NMR in natural products: understanding conformation, configuration and receptor interactions - Carlomagno, Teresa (Natural product reports, 2012)
Covering: up to 2011 Natural products are of tremendous importance in both traditional and modern medicine. For medicinal chemistry natural products represent a challenge, as their chemical synthesis and modification are complex processes, which require many, often stereo-selective, synthetic steps. A prerequisite for the design of analogs of natural products, with more accessible synthetic routes, is the availability of their bioactive conformation. Nuclear Magnetic Resonance (NMR) spectroscopy and X-ray crystallography are the two techniques of choice to investigate the structure of natural products. In this review, I describe the most recent advances in NMR to study the conformation of natural products either free in solution or bound to their cellular receptors. In chapter 2, I focus on the use of residual dipolar couplings (RDC). On the basis of a few examples, I discuss the benefit of complementing classical NMR parameters, such as NOEs and scalar couplings, with dipolar couplings to simultaneously determine both the conformation and the relative configuration of natural products in solution. Chapter 3 is dedicated to the study of the structure of natural products in complex with their cellular receptors and is further divided in two sections. In the first section, I describe two solution-state NMR methodologies to investigate the binding mode of low-affinity ligands to macromolecular receptors. The first approach, INPHARMA (Interligand Noes for PHArmacophore Mapping), is based on the observation of interligand NOEs between two small molecules binding competitively to a common receptor. INPHARMA reveals the relative binding mode of the two ligands, thus allowing ligand superimposition. The second approach is based on paramagnetic relaxation enhancement (PRE) of ligand resonances in the presence of a receptor containing a paramagnetic center. In the second section, I focus on solid-state NMR spectroscopy as a tool to access the bioactive conformation of natural products in complex with macromolecular receptors.